2003
DOI: 10.1097/00008506-200301000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Increased Cerebral Perfusion as Compared With Isoflurane During a Cerebral Angiography in a Child With Moyamoya Disease

Abstract: We report the case of a child with Moyamoya disease during a cerebral angiography procedure in which the effects of propofol on the cerebral perfusion were seen to be different compared with isoflurane. We suggest propofol was associated with a better preservation of cerebral circulation compared to isoflurane in this case of Moyamoya, as it maintained blood supply to the watershed areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous reports on the influence of different anesthetic methods on the occurrence of TNEs have suggested that the preoperative severity of illness and the surgical technique may be related to postoperative neurological symptoms, with no differences because of inhalation and intravenous anesthesia. [9][10][11][12] However, these findings remain a subject of debate. Some have suggested that TIVA using propofol, which lacks cerebral vasodilatory properties, may be better suited for maintaining CBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on the influence of different anesthetic methods on the occurrence of TNEs have suggested that the preoperative severity of illness and the surgical technique may be related to postoperative neurological symptoms, with no differences because of inhalation and intravenous anesthesia. [9][10][11][12] However, these findings remain a subject of debate. Some have suggested that TIVA using propofol, which lacks cerebral vasodilatory properties, may be better suited for maintaining CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have reported no significant differences between inhalational and intravenous anesthesia methods. [9][10][11][12] Conversely, it has been demonstrated that intravenous anesthesia is better suited for maintaining regional CBF because inhalation anesthesia (IA) tends to dilate cerebral blood vessels and increase intracranial pressure, potentially leading to cerebral steal phenomena intraoperatively. 13 In light of recent advancements in anesthesia methods, this study aimed to examine whether contemporary anesthesia methods influence the occurrence of postoperative neurological symptoms, with a specific focus on transient neurological events (TNEs).…”
mentioning
confidence: 99%
“…The effects of inhalational anesthesia on the cerebral circulation in patients who are undergoing revascularization procedures for moyamoya disease were reported to be decreased regional cortical blood flow, increased jugular bulb oxygen saturation and decreased frontal regional oxygen saturation, whereas these effects did not occur with total intravenous anesthesia [10]. Propofol was associated with better preservation of the cerebral circulation as compared to that of isoflurane in the case of a child with moyamoya disease during a cerebral angiography procedure [11]. The optimal range of CO 2 for isoflurane is more restricted than that for propofol and presumably because isoflurane induces hyperemia by itself and this hyperemia decreases the cerebral blood flow [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although several published case reports and retrospective studies have compared the effects of total IV anesthesia and inhaled anesthesia on neurologic outcomes of pediatric patients with moyamoya, no particular anesthetic has been shown to reduce the risk of neurologic complications. 17,[31][32][33][34][35] To our knowledge, various volatile gas anesthetics have not been compared in pediatric patients with moyamoya in a randomized study. Therefore, we are unable to make recommendations on specific anesthetic regimens but rather outline our general intraoperative approach.…”
Section: Intraoperativementioning
confidence: 99%